Students` Perceptions of YouTube Videos as a Tool for Developing Listening Skills - Aqmarina, Amanda Zatil; Authar, Nailul; Afandi, Mujad Didien; Aquariza, Novi Rahmania; Basuki, Edi Pujo (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study explores college students’ perceptions of using YouTube videos as a tool to enhance their listening skills. With the rapid integration of digital media into education, YouTube has become a widely accessible and valuable resource for language learning. The study adopts a qualitative approach by collecting data through semi-structured interviews and focus group discussions involving students who actively use YouTube for English listening practice. The findings, analyzed using thematic analysis, reveal several advantages of YouTube as a learning medium. Students report that it provides exposure to authentic language use, a wide variety of accents, and flexible features such as adjustable playback speed, which help improve comprehension. Additionally, the platform allows learners to access diverse topics that match their interests, increasing engagement and motivation. However, the study also identifies several challenges faced by students. Many participants find it difficult to select appropriate and level-appropriate content due to the vast amount of videos available. Furthermore, distractions from unrelated or entertaining content often reduce learning effectiveness. These issues indicate that while YouTube offers significant potential as a supplementary tool for improving listening skills, its success largely depends on students’ ability to manage their learning process. Overall, the study concludes that YouTube can effectively support listening skill development when used strategically. Therefore, educators are encouraged to guide students in selecting suitable content and developing focused learning habits to maximize the educational benefits of YouTube.